Clinicopathological Characteristics and Mutational Landscape of APC, HOXB13, and KRAS among Rwandan Patients with Colorectal Cancer - Felix Manirakiza; Eric Rutaganda; Hidetaka Yamada; Yuji Iwashita; Belson Rugwizangoga; Benoit Seminega; Vincent Dusabejambo; Gervais Ntakirutimana; Deogratias Ruhangaza; Annette Uwineza; Kazuya Shinmura; Haruhiko Sugimura (Current Issues in Molecular Biology, 2023)
Cancer research in Rwanda is estimated to be less than 1% of the total African cancer research output with limited research on colorectal cancer (CRC). Rwandan patients with CRC are young, with more females being affected than males, and most patients present with advanced disease. Considering the paucity of oncological genetic studies in this population, we investigated the mutational status of CRC tissues, focusing on the Adenomatous polyposis coli (APC), Kirsten rat sarcoma (KRAS), and Homeobox B13 (HOXB13) genes. Our aim was to determine whether there were any differences between Rwandan patients and other populations. To do so, we performed Sanger sequencing of the DNA extracted from formalin-fixed paraffin-embedded adenocarcinoma samples from 54 patients (mean age: 60 years). Most tumors were located in the rectum (83.3%), and 92.6% of the tumors were low-grade. Most patients (70.4%) reported never smoking, and 61.1% of patients had consumed alcohol. We identified 27 variants of APC, including 3 novel mutations (c.4310_4319delAAACACCTCC, c.4463_4470delinsA, and c.4506_4507delT). All three novel mutations are classified as deleterious by MutationTaster2021. We found four synonymous variants (c.330C>A, c.366C>T, c.513T>C, and c.735G>A) of HOXB13. For KRAS, we found six variants (Asp173, Gly13Asp, Gly12Ala, Gly12Asp, Gly12Val, and Gln61His), the last four of which are pathogenic. In conclusion, here we contribute new genetic variation data and provide clinicopathological information pertinent to CRC in Rwanda.